263 Characterizing Vaginal Bacterial Community Composition in Brangus Heifers. (8th October 2021) - Messman, Riley D; Contreras-Correa, Zully E; Paz, Henry A; Lemley, Caleb O
Abstract: The role of the reproductive tract microbiota is an emerging field receiving considerable attention in human research, whereby the vaginal microbiota has been characterized in relation to fertility, conception, pregnancy, and parturition. However, the acidic, Lactobaccillus dominated vaginal microbiota in humans contrasts the neutral, dynamic microbial environment characterized in cattle. Over the past few years, many postpartum studies in dairy cattle described a mechanism recently proposed in humans, the ascension of the vaginal microbiota into the uterine body at the onset of labor. Although bovine fetal sterility prior to parturition is under debate, the vaginal microbiota is an early contact for the neonate with microorganisms and inoculates the uterus during parturition. Thus, any changes occurring in the vaginal microbiota could have implications in dam and calf health; this, combined with ease of access, led to the current research focusing on the bovine vaginal microbiota. Characterization studies during the estrous cycle, gestation, and postpartum period have been performed, concluding the bovine vaginal microbiota is dynamic. However, due to the low abundance in the vaginal microbiota, the seemingly small taxonomic changes reported in these studies could be of great importance. Secondly, researchers have begun to evaluate the effect of exogenous and endogenous hormone concentrations on the vaginal microbiota. Little to no differences have been found except with exogenous melatonin supplementation. In pregnant heifers, exogenous melatonin altered the beta diversity of the vaginal tract by increasing aerobic bacteria present. Moreover, a study evaluating the effects of nutrient restriction on the vaginal microbiota found no taxonomic or structure differences. These findings have allowed researchers to target paucities, improve methodology, and realize the importance of the reproductive tract microbiota. In short, based on these studies, future research examining the role of the reproductive tract microbiota could uncover mechanisms vital to increasing reproductive performance.